2021
DOI: 10.1155/2021/3601509
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Convection Heat Transfer and Fluid Dynamics in Microchannels with Arrayed Microgrooves

Abstract: The analysis of heat transfer and fluid dynamics in a microchannel is currently one of numerous important research areas. The present study investigated the heat transfer and fluid dynamics in a microchannel with arrayed microgrooves. The boundary conditions in the microchannel and microgrooves were the velocity slip condition and temperature jump condition. The numerical calculations in the present study were based on a new numerical analysis scheme that was used to name modified point-matching methods. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A numerical approach for the thermophoretic and heat source impacts on micropolar fluid with a magnetic field was provided by Sharma et al [ 38 ]. The convective heat transfer flow in micropolar fluid arrayed with microgrooves was analyzed by Hu et al [ 39 ]. An exponential study of convective heat transfer in mono-hybrid nano-fluids was demonstrated by Vallaj et al [ 40 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…A numerical approach for the thermophoretic and heat source impacts on micropolar fluid with a magnetic field was provided by Sharma et al [ 38 ]. The convective heat transfer flow in micropolar fluid arrayed with microgrooves was analyzed by Hu et al [ 39 ]. An exponential study of convective heat transfer in mono-hybrid nano-fluids was demonstrated by Vallaj et al [ 40 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%